THE KITSILANO SCANDAL: The Destruction of Senáḵw as Told in Local Newspapers, 1913-16. - SLOBODIAN, MAYANA C. (BC Studies)
The article looks at the 1913 destruction of the Sen'ákw Squamish Tribe village located at the Kitsilano Indian Reserve in Vancouver, British Columbia. Topics include how life at the village began to change in late 1800s, its designation as Kitsilano Indian Reserve No. 6 in 1877 by the Joint Indian Reserve Commission, and an account of an illegal action against the village taken by the attorney general during the launch of a joint federal and provincial Royal Commission on Indian Affairs.